2022
DOI: 10.3390/jcm11133643
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Comorbidity between Dry Eye and Allergic Conjunctivitis: A Systematic Review and Meta-Analysis

Abstract: This systematic review aimed to determine the comorbid dry eye (DE) and allergic conjunctivitis (AC) prevalence. We searched PubMed and EMBASE for articles published until 22 March 2022, combining the terms “(dry eye OR keratoconjunctivitis sicca) AND allergic conjunctivitis.” Study-specific estimates (DE and AC incidence rates among patients with AC and DE, respectively) were combined using the one-group meta-analysis in a random-effects model. The initial search yielded 700 studies. Five articles reporting A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…In a recent systematic review and meta-analysis including studies on ocular allergy and dry eye, it was found that 47.2% of the patients with AC exhibited comorbid dry eyes. [ 20 ] There is no published study on the association of AC and DED in north India which makes this study unique. Most of the studies done on AC included SAC & PAC as one entity, but in our study, we studied both the groups separately and found that in this region SAC (69/132 patients) is the most common AC.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review and meta-analysis including studies on ocular allergy and dry eye, it was found that 47.2% of the patients with AC exhibited comorbid dry eyes. [ 20 ] There is no published study on the association of AC and DED in north India which makes this study unique. Most of the studies done on AC included SAC & PAC as one entity, but in our study, we studied both the groups separately and found that in this region SAC (69/132 patients) is the most common AC.…”
Section: Discussionmentioning
confidence: 99%
“…DE had co-morbid AC. 21 Nevertheless, allergic reactions secondary to SED are infrequently described. Only Lekhanont et al 5 recorded what they considered to be an allergic reaction to SED-which was autologous!…”
Section: Discussionmentioning
confidence: 99%
“…Allergic eye disease commonly follows exposure to environmental allergens, such as pollen and dust mites, followed by binding of antigen by specific IgE on the surface of conjunctival mast cells, and then mast cell degranulation 20 . Furthermore, a study found that dry eye (DE) is a frequent co‐morbidity in patients with allergic conjunctivitis (AC) and vice versa: the authors estimated that 17.8% of those with DE had co‐morbid AC 21 . Nevertheless, allergic reactions secondary to SED are infrequently described.…”
Section: Discussionmentioning
confidence: 99%
“…(1) patients with other types of AC, including AKC, VKC, and GPC; (2) patients who underwent any other infectious in ammation or ocular immunological diseases other than SAC/PAC and DE, such as uveitis, blepharitis, Sjögren's syndrome (SS) and ocular graft-versus-host disease (oGVHD), etc. 3 individuals who had undergone ocular surgery within three months preceding the trial; (4) patients using topical or systemic steroid, anti-allergic or immunosuppressive drugs within one month of inclusion in the study; (5) For tear proteomics analysis, we further excluded subjects with insu cient tear sample size.…”
Section: • Study Design and Participantsmentioning
confidence: 99%
“…2,3 Studies have shown that the prevalence of DE in patients with AC is 31.3% and even up to 47.2% in a recent meta-analysis. 4,5 In southwest China, the prevalence of DE among children with AC has reached 97.5%. 6 Previously, the major treatment options required a combination of multiple medications.…”
Section: Introductionmentioning
confidence: 99%